The Final Message of God : The Substance of the Holy Quran - Compiled by Rizavi, M. N. (Islamabad Modern Book Depot, 2002)
Include Annex and Appendices.
The Substance of the Holy Quran : Arranged Topic-Wise
Keywords: Qurʼan -- Islam--Doctrines